Effectiveness of project and program aid in improving quality of life - KIM, Jaewon (KDI School, 2018)
The purpose of this study is to find out which aid modality between project and program aid is more effective for enhancing the quality of life in recipient countries with different levels of income. It connects the two major topics in aid effectiveness: (1) effectiveness of different aid modalities, and (2) aid effectiveness regarding the promotion of overall quality of life of the recipients. Panel data between 2004 and 2015 was used to compare the impact of two aid modalities on the improvement of overall welfare, and on economic growth, which is the traditional indicator. Results of the study indicate that it is recommended to give more program aid to lower middle income countries (LMICs) rather than least developed countries (LDCs), while LDCs are more adaptive to the project aids
Thesis(Master) --KDI School:Master of Development Policy,2018